Research Output of University of Jaffna, Sri Lanka during 2000-2019 - Janen, T. (Defence Scientific Information & Documentation Centre, 2021)
Universities play a vital role in the research and development of a country. A scientometric analysis is an essential tool used by the administrators, funding agencies, government, and researchers to know the publication trend on a topic, institution, author, journal, etc. This study analyses pattern of articles published by the University of Jaffna (UoJ) during 2000-2019; identifies publication growth rate, most prolific authors and their citation impact, communication pattern in terms of type of documents, journal publishing country and impact factor of these journals and also the international collaboration. Analysis of the data indicates, there are 293 articles were published in WOS indexed journals. The publication growth rate indicates that there is a consistent growth in the number of publications after 2014. It was found that multi-authorship dominates among UoJ researchers. A high number of publications were on Multidisciplinary Sciences. The UoJ collaborated with different countries; among them 59 articles were published with United Kingdom. Among the highly cited top 10 publications, an article authored by Ravirajan P received a high number of citations of 480. Among the funding agencies National Science Foundation of Sri Lanka funded for 24 publications, while UoJ funded for 16 and among the international funding agencies UK Research Innovation (UKRI) funded for 7 publications during the study period.
Keywords: University of Jaffna; Scientometric analysis; Research trend; Authorship analysis; Productive author